RECRUITMENT SCHEME OF INVESTIGATORS IN THE DIRECTORATE OF GENERAL CRIME AT THE INDONESIA NATIONAL POLICE THROUGH THE TALENT SCOUTING STRATEGY - Kevin Asshabul Kahfi,; Surya Nita,; Firmah Fadilla, (International Journal of Innovative Technologies in Social Science, 2022)
The police are law enforcement officers who are given the authority to conduct investigations into criminal cases. The ability of investigators then determines the success of law enforcement. Recruitment of investigators working at the Directorate of General Crime at INP then needs to be done properly, so implementing talent scouting is the organization's choice. This paper aims to analyze the investigator recruitment scheme in one of the functions of the INP, namely the Directorate of General Crimes at the Criminal Investigation Agency by applying the concept of talent scouting. The method used in this research is descriptive research with a qualitative approach. Data was collected by literature study and documentation study. Secondary data sources are taken from books, journals, internal documents and others related to research problems. An interactive analytical framework was employed to analyze the data. The results of the study show that the implementation of talent scouting can be carried out by carrying out five stages: 1) announcement, 2) determination of eligible participants, 3) registration, 4) administrative selection, 5) competence test to get a talent pool. The two main factors that influence the recruitment of investigators are internally, the readiness of the INP General Crimes Directorate and externally the readiness of candidates to register and carry out tests.